Author Correction: Bacterial nanotubes as a manifestation of cell death - Pospíšil, Jiří; Vítovská, Dragana; Kofroňová, Olga; Muchová, Katarína; Šanderová, Hana; Hubálek, Martin; Šiková, Michaela; Modrák, Martin; Benada, Oldřich; Barák, Imrich; Krásný, Libor (Nature communications, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.